Platelet-Rich Plasma and Its Role in Wound Healing After Dental Procedures: A Literature Review - Rafałowska, Julia; Sajda, Małgorzata; Woźniak, Martyna; Sikora, Gabriela; Kutnik, Karolina; Koguc, Karolina; Kusibab, Karolina; Czechowski, Michał; Skórska, Gabriela; Słomianny, Marcela; Kolada, Karolina (Quality in Sport, 2025)
Introduction Platelet-rich plasma (PRP) is an autologous blood-derived preparation whose task is to release growth factors from platelets that support the regeneration of damaged tissues. The development of medicine has made PRP increasingly common in various fields of science, including dentistry. The widespread use of plasma in dental surgery, maxillofacial surgery, periodontology and even pedodontics has increased the percentage of positive treatment results and increased therapeutic possibilities. Materials and Methods: The literature review was conducted using the PubMed database. Publications from 2000–2025 were searched. The literature review included various types of publications such as narrative and systematic reviews, randomized controlled trials (RCTs), cohort studies, meta-analyses, and expert consensus papers. Results: A review of the literature revealed that platelet-rich plasma (PRP) significantly supports tissue regeneration and healing following dental procedures. Clinical studies demonstrated reduced postoperative pain and swelling, accelerated wound closure, and improved bone density in sites treated with PRP. Positive outcomes were observed across multiple dental disciplines, including oral surgery, maxillofacial reconstruction, periodontology, and pediatric dentistry. Additionally, PRP was shown to stimulate angiogenesis, modulate inflammation, and promote cellular proliferation, while exhibiting antimicrobial properties. However, variation in study protocols and outcomes suggests the need for cautious interpretation.